Assessment of patients presented to the emergency department with dermatological complaints: Retrospective cohort study - Nazik, Hülya; Hakkoymaz, Hakan (Journal of Surgery and Medicine, 2019)
Aim: Although dermatology is an area of expertise based largely on outpatient treatment, about 5-10% of emergency department patients are dermatological diseases. In this study, it was aimed to draw attention to management of dermatologic diseases which are frequently encountered in emergency services. Methods: Over 18 years old 96 patients who presented with a dermatologic problem to the emergency department of Kahramanmaras Sutcu Imam University Hospital between January and June 2018 were evaluated. Results: The mean age of the patients was 43.9 ± 17.1 years. When the gender distribution was examined, 39.6% (n=38) of the cases were male and 60.4% (n=58) were female. Pruritus and rash were the most common dermatological complaints and the most common diagnoses were urticaria (38.5%), urticaria-angioedema (13.5%), cellulitis (8.3%) and anaphylaxis (8.3%) in this study. The rate of cases without known dermatological disease was 77.1%. In 52 (54.2%) cases, there was a new drug use which may be associated with the current dermatosis, and antibiotics (22.9%) were the most frequently detected from these drugs. Conclusion: It was seen that most of the patients who admitted with a dermatological problem had no known dermatological disease, and some adult patients with chronic dermatosis might apply to emergency services. It has been determined that not all cases are real dermatologic emergencies and most of them are relieved and discharged by intervention made at the emergency department without need of examination. The presence of a new drug use in about half of the cases revealed that drugs are an important etiologic factor in emergency dermatological diseases.